Ideology and the maintenance of group inequality. (September 2017) - Major, Brenda; Kaiser, Cheryl R.
This article discusses the role that ideology plays in justifying and perpetuating group-based inequality. We begin by defining and describing status ideologies and their characteristics. We then review research illustrating how endorsing or rejecting status-legitimizing ideologies influences group stereotyping, group differences in perceived entitlement, and perceptions of discrimination. We next discuss how people respond to threats to their status ideology, affectively, cognitively, physiologically, and behaviorally. We close by considering the role of ideology in how high status groups respond to changes in the status hierarchy.